Comparative expression profiling of Portuguese and Turkish Behçet syndrome patients: Are we looking at the same Behçet? - Tulin Isik; Seda Tasir; Abdulfettah Zolkhfan; Cagdas Sahap Oygur; Ali Kemal Oguz (European Journal of Inflammation)
Background: Behçet syndrome (BS) is a multisystemic inflammatory disorder with an obscure pathogenesis. Inconsistent, sometimes contrasting immunological findings observed in BS studies and considerable geographic variation in BS’s disease expression need explanation. This study compared the gene expression profiles of Portuguese and Turkish BS patients. Methods: Publicly available transcriptome datasets from Portuguese (GSE17114) and Turkish (GSE209567) BS cohorts were retrieved and analyzed. Behçet syndrome patients were grouped as mucocutaneous, ocular, and vascular. Differentially expressed genes (DEGs) were identified using p ≤ 0.05 and fold-changes (FC) ≥1.5 and ≥2. BRB-ArrayTools for class comparisons, Venny 2.1.0 for Venn diagram analyses, Cluster 3.0 and Java Treeview for clustering, and WebGestalt for functional enrichment analyses were used. Results: During the class comparison PB versus TB (PB: Portuguese and TB: Turkish BS patients), 8024 DEGs were documented with an FC ≥2. Venn diagram analysis showed no shared genes at the intersection PB versus PC ∩ TB versus TC (PC: Portuguese and TC: Turkish controls). Both populations demonstrated decreased anti-inflammatory gene expressions, albeit with distinct gene identities. A set of 20 genes including IFI27 successfully clustered PB & TB. No enriched gene ontology terms were shared during functional enrichment analyses. Conclusion: Significant molecular differences exist between Portuguese and Turkish BS patients. Decreased expression of anti-inflammatory genes (e.g., CD69 , CLEC12A , CLC ) is common in BS. The identities of these genes are different across populations. Pro-inflammatory genes (e.g., IFI27 ) may further enhance disease severity in BS. A forthcoming era of personalized therapeutics based on molecular profiles may be approaching for BS. Specifically, CD69 for Portuguese and CLEC12A , CLC , and IFI27 genes for Turkish BS patients, may prove to be promising drug targets for BS.